MONITORING DAN PENGENDALIAN SUHU MENGGUNAKAN MEDIA GPRS PADA PONSEL GSM - -, Subandi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
The temperature forms the importan aspect on the life. There are a lot of activity which was under the influence of the condition of temperature. Because of that, monitoring system and controlling the temperature is necessary. Therefore, making the equipment which able to monitor and control the temperature is necessary. This interface will applied on the room where needs controlling the temperature. For example, laboratory or meeting room. Monitor and controller in wireless manner become choice on the controlling long distance. This analysis heavily on the activity of temperature censor and relay which be connected on the fan for the stimulation. The temperature of the room information and send to microcontroller what will work by automatically contact the PC through LPT or port printer for the parallel communication. All of the data will be processing and connecting to the web as an internet aplication on the PC. We can choice menu to control and monitor temperature of the room through GPRS media on the GSM telephone cellular from the connection of the internet. Microcontroller which used is microcontroller AT89S51.